2008
DOI: 10.1007/s11663-008-9166-2
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Analysis of Coarsening during Directional Solidification Experiments in High-Solute Aluminum Alloys

Abstract: Coarsening within the mushy zone during continuous directional solidification experiments was studied on an Al-30 wt pct Cu alloy. High brilliance synchrotron X-radiation microscopy allowed images to be taken in-situ during solidification. Transient conditions were present during directional solidification. Under these conditions, solute-rich settling liquid flow affects the dendritic array and thus coarsening. Coarsening was studied by following the secondary dendrite arm spacing (SDAS) of a developing dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…[5] through [7], k 1 and k 2 are closely related with G and V, therefore N d can be related with G and V and the relation is shown in Eq. [9]:…”
Section: Interpretation Of the Results Based On The Fragmentation mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] through [7], k 1 and k 2 are closely related with G and V, therefore N d can be related with G and V and the relation is shown in Eq. [9]:…”
Section: Interpretation Of the Results Based On The Fragmentation mentioning
confidence: 99%
“…Remelting of tertiary branches at the root to the parent dendrite remains a better pathway for dendrite detachment. Previous to the dendrite fragmentation by remelting, a minor deceleration [9] of the columnar front velocity is noticeable. Ruvalcaba et al hypothesized that this deceleration would induce enhancement of solute at the columnar front and subsequently the solute-rich liquid will settle into the mush and initiate dendrite detachment.…”
Section: Introductionmentioning
confidence: 99%
“…Because the flow velocity vector v i and the EM braking force f i interact with each other under an externally applied magnetic field B i , Eq. [38] has been coupled with Eq. [30] via the body force term X i : Thus, Eq.…”
Section: B Effects Of Static Magnetic Field On Interdendritic Liquidmentioning
confidence: 99%
“…Also, it is well known that columnar dendrites grow toward the upstream side of the liquid flow at solidification front, which has been interpreted by constitutional supercooling theory [36] : Tan and Zabaras [37] have shown this by the numerical simulation of an alloy dendritic solidification (see Figures 2.4 and 2.5 of Reference 37). Incidentally, Ruvalcaba et al [38] have carried out the in situ observations during downward DS (liquid density inversion within the mushy zone) of an Al-Cu alloy by means of X-ray microscopy, and they have shown that where the primary dendrite arm spacing becomes uneven, the growth rates of secondary dendrite arms perpendicular to the growth direction exhibit the difference. Although the detailed mechanism is not known, the liquid flow in the mushy zone is considered responsible for this difference.…”
Section: A Transverse Magnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation